THE RIGHT TO LIFE: MODERN MEDICAL AND LEGAL CONTEXT - Sovgyria, O.; Yanchuk, A. (World of Medicine and Biology, 2018)
The study characterizes modern medical and legal aspects of the right to life, including: the time limits of the concept of "life" and the woman’s right to decide on the termination of pregnancy (the right to abortion) of euthanasia (in particular, children’s), the use of embryos for medical purposes; reproductive technologies, cloning, surrogate motherhood. Іn terms of the characteristic of the problem of legal regulation of transplantation in Ukraine, the most important international standards are presented, the legislation of Ukraine is analyzed, ways of overcoming the problems of legal regulation are determined. The model of organization of transplants in Spain has also been analyzed. This model has its name - MODELO ESPAÑOL (Spanish model) and recommended by WHO as exemplary for use in other states.